2007
DOI: 10.1021/ma0702290
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Poly(dialkylsiloxane) Melts:  Comparisons of Wide-Angle X-ray Scattering, Molecular Dynamics Simulations, and Integral Equation Theory

Abstract: Wide-angle X-ray scattering, molecular dynamics (MD) simulations, and integral equation theory are used to study the structure of poly(diethylsiloxane) (PDES), poly(ethylmethylsiloxane) (PEMS), and poly-(dimethylsiloxane) (PDMS) melts. The structure functions of PDES, PEMS, and PDMS are similar, but systematic trends in the intermolecular packing are observed. The local intramolecular structure is extracted from the experimental structure functions. The bond distances and bond angles obtained, including the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…As anticipated from T g measurements of PDMS in the solid-state [ 10 , 18 ], we find that a polysiloxane backbone yields fast LRPCD in solution. Furthermore, this study confirms that the Model Free Analysis of TRF decays of polymers randomly labeled with pyrene yields reliable and quantitative information about the relative magnitudes of the dynamic processes experienced by different polymeric chains in solution.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As anticipated from T g measurements of PDMS in the solid-state [ 10 , 18 ], we find that a polysiloxane backbone yields fast LRPCD in solution. Furthermore, this study confirms that the Model Free Analysis of TRF decays of polymers randomly labeled with pyrene yields reliable and quantitative information about the relative magnitudes of the dynamic processes experienced by different polymeric chains in solution.…”
Section: Discussionsupporting
confidence: 83%
“…While it is reasonable and expected that < k MF > blob for PDMS, a polymer well-known for its flexibility [10,18], is greater than for PS in THF, the 2.9 fold difference is much smaller than that reported for the dynamics of pyrene end-labeled monodisperse PDMS and PS polymers in toluene [19]. Thus, the fact that the LRPCD probed by PDMS constructs that are monodisperse and end-labeled are thrice the value for polydisperse and randomly labeled PDMS with pyrene may be a consequence of the different bond angles of the PDMS backbone: the Si–O–Si bond angle is 146° whereas that of O–Si–O is 108° [18]. This difference implies that a PDMS chain in its most energetically stable all trans -conformation would be coiled, whereas the backbone of a PS chain in the same all trans -conformation would be fully extended because its C–C–C bond angles are near 109°.…”
Section: Resultsmentioning
confidence: 99%
“…In experimental and simulation XRD studies on PDMS melt structures, a broad peak has been observed at q = 0.85 Å −1 (where q = 4π sin θ /λ) which for CuK α radiation corresponds to 2 θ ~ 12°. This peak has been attributed to intermolecular correlations in liquid state PDMS chains in bulk 40 , 41 , where chains are relatively ordered in liquid state. In our case, a nano-scale confinement due to hydrophilic PVA, the intermolecular distance could further be reduced and lead to a reflection at an increased value of 2 θ .…”
Section: Resultsmentioning
confidence: 99%
“…It is recognized that these initial dense-phase models do not yet represent a truly equilibrated structure of the polymer. Additional advanced sampling algorithms are needed and are being planned to attain this level of equilibration, with the equilibrated polymer structures to be validated by comparing RDFs from the polymer model with RDFs obtained by wide-angle x-ray scattering (WAXS) measurements [38, 39]. The present work sets the stage from which these further studies can be implemented to attain our final objective of producing accurate dense-phase all-atom models of complex amorphous polymers, which can then be used as a guide for polymer design to optimize performance for targeted applications.…”
Section: Discussionmentioning
confidence: 99%